1984
DOI: 10.2337/diab.33.8.717
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Type I Diabetes: Linear Loss of Beta Cell Response to Intravenous Glucose

Abstract: Twenty-one intravenous (i.v.) glucose tolerance tests were performed on nine subjects before the onset of overt type I diabetes mellitus. Islet cell antibodies (6 of 9 subjects) and elevated levels of Ia-positive T-lymphocytes (3 of 3 subjects studied) were detected during the prediabetic period. Elevations of fasting blood glucose and peak glucose during oral glucose tolerance tests were not observed until the year before onset of clinically overt diabetes. During the prediabetic period, there was a progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
1
1

Year Published

1987
1987
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(96 citation statements)
references
References 5 publications
2
92
1
1
Order By: Relevance
“…Immediately thereafter, 0.5 g glucose per kg of body weight (maximum: 35 g) as a 40% aqueous solution was infused into the second cannula within 3 min±15 s. Serum insulin and C-peptide levels at time points 1 and 3 min were used for calculation of the first-phase insulin response (FPIR). The results were evaluated according to published standards [9,18].…”
Section: Testing Proceduresmentioning
confidence: 99%
“…Immediately thereafter, 0.5 g glucose per kg of body weight (maximum: 35 g) as a 40% aqueous solution was infused into the second cannula within 3 min±15 s. Serum insulin and C-peptide levels at time points 1 and 3 min were used for calculation of the first-phase insulin response (FPIR). The results were evaluated according to published standards [9,18].…”
Section: Testing Proceduresmentioning
confidence: 99%
“…The advantage of an intravenous test is the lack of influence of the entero-insulineric axis. The standard intravenous glucose tolerance test predominantly provides information about the early insulin secretion phase [16]. The GIT used in this study with our newly provided reference values, established in the same laboratory, accurately evaluated hyperinsulinemia induced by growth hormone therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The cystine content of leukocytes was normal. Using the method described by Srikanta et al [8], an IV glucose tolerance test (IVGTT) performed before rhGH treatment revealed normal glucose tolerance (k=2.65). Both early and total insulin secretion and reactive C-peptide production (actual Cpeptide concentration minus average baseline concentration before glucose infusion) were within the range of 15 control prepubertal patients with a similar degree of renal insufficiency (Fig.…”
Section: Case Reportmentioning
confidence: 99%